Advances in ultra-low emission control technologies for coal-fired power plants - Zhang, Yongsheng; Wang, Tao; Pan, Wei-Ping; Romero, Carlos E. (Woodhead Publishing in energy., 2019)
Advances in Ultra-low Emission Control Technologies for Coal-Fired Power Plants discusses the emissions standards of dust, SO2, NOx and mercury pollution, also presenting the key technologies available to control emissions in coal-fired power plants. The practical effects of ultra-low emissions projects included help the reader understand related implications in plants. Emphasis is placed on 300MW subcritical, 600MW subcritical, 660MW supercritical and 1000MW ultra-supercritical coal-fired units. The influence of different pollutant control units, such as wet electrostatic precipitator, desulfurization equipment and the electrostatic precipitator are also analyzed, and the pollutant levels before and after retrofitted ultra-low emissions are compared throughout.